Memanfaatkan Sosial Media untuk Meningkatkan Kesadaran PTSD - Nugroho, Julius Andi; Andreas; Meilyana Chayadi; Lienardy, Bianca Julita; Vania Aurelia (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Paramadina, 2024)
Post-traumatic stress disorder (PTSD) is a mental health condition that's triggered by a terrifying event either experiencing it or witnessing it. Symptoms may include flashbacks, nightmares, and severe anxiety, as well as uncontrollable thoughts about the event. There have been many case studies about PTSD (Post-Traumatic Stress Disorder). PTSD itself is a mental disorder that appears after a person experiences or witnesses an unpleasant moment. It is stated that PTSD symptoms are shown during the teenage period at around the age of 12-19 years old because, in this current time, adolescents tend to show impulsive or aggressive behavior. The problem lies in the fact that teenagers are not aware of such symptoms as trauma reactions which if left unchecked, will only get worse. We devise a social media platform that can help decrease the burden of teenagers dealing with PTSD symptoms. Adding knowledge and increasing awareness is also our goal in creating the media platform. Recognizing this critical need, we envision a social media platform specifically designed to address the challenges faced by teenagers grappling with PTSD. This platform wouldn't be just another digital landscape; it would be a lighthouse piercing the storm, a safe harbor where understanding and support converge.